2020
DOI: 10.1111/den.13679
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux metal stent for biliary obstruction: Any benefits?

Abstract: Endoscopic retrograde cholangiopancreatography with stent placement has been utilized as standard palliative management of distal malignant biliary obstruction (MBO). Compared to plastic stents, metal stents can provide longer‐term relief of symptoms. When a large‐bore metal stent is placed across the ampulla, patients are predisposed to the risk of cholangitis or stent dysfunction due to reflux of duodenal contents. To mitigate the risk of adverse events associated with the duodenobiliary reflux, efforts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 124 publications
1
14
0
Order By: Relevance
“…23 Therefore, further improvement is required to develop the most appropriate ARMS. 24 In the present study, the technical success rate and functional success rate of biliary stenting using D-ARMS were 93% and 87%, respectively. These values are comparable to previous reports, suggesting that D-ARMS is feasible for biliary stenting.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…23 Therefore, further improvement is required to develop the most appropriate ARMS. 24 In the present study, the technical success rate and functional success rate of biliary stenting using D-ARMS were 93% and 87%, respectively. These values are comparable to previous reports, suggesting that D-ARMS is feasible for biliary stenting.…”
Section: Discussionsupporting
confidence: 45%
“…Their study demonstrated that a duodenal pH environment induced a morphological change of ARV leading to stent dysfunction 23 . Therefore, further improvement is required to develop the most appropriate ARMS 24 …”
Section: Discussionmentioning
confidence: 99%
“…There are two treatment options to prevent duodenobiliary reflux itself; anti-reflux stents and stent above the papilla. Clinical trials of anti-reflux biliary stents have been conducted, but their role is still controversial [8]. Stents above the papilla, so-called "inside stents," have been investigated using both metal and plastic stents [9].…”
Section: Introductionmentioning
confidence: 99%
“…FCSEMSs are usually designed with a larger diameter to a have longer patency period. However, this design also results in a reflux of duodenal contents, leading to cholangitis and sludge occlusion [42]. For MPSs, cholangitis resulting from frequent interventions was the most common adverse event.…”
Section: Discussionmentioning
confidence: 99%